A sequential simulation strategy for response bounds analysis of structures with interval uncertainties. (1st July 2022) - Ni, B.Y.; Jiang, C.; Wu, P.G.; Wang, Z.H.; Tian, W.Y.
Highlights: The upper and lower response bounds are obtained through a series of sequential simulations. The proposed sequential simulation method is applicable to interval uncertainty analysis of structural or system response with multiple DOFs. The contributive samples for the response bounds over the whole concerned domain can be identified simultaneously. The sequential simulation strategy is demonstrated to be more efficient than the direct MC simulation for response bounds evaluation. Abstract: Prediction of response bounds of structures with interval uncertainties is a major concern in interval finite element analysis. In many cases, the structural response is a variable regarding to physical parameters such as location, node, time, or other degrees of freedom. Different kinds of interval methods have been proposed and developed for response bounds analysis, which mainly include the interval arithmetic-based methods, optimization methods, perturbation methods, etc. This paper proposes a sequential simulation strategy for response bounds analysis of structures with interval uncertainties, through which we aim to find the upper and lower bounds by implementing the simulation procedure sequentially. The proposed sequential simulation strategy suggests an initial sampling and simulation, from which those contributive samples that result in the current upper or lower response bound are retained. In the subsequent simulation sequence, local samples within neighborhoods of the present contributive samples as well as a set of global samples are generated for the input interval uncertainties. With such a simulation procedure, the response bounds are expected to expand outwards sequentially until convergence. By illustration and comparison, the proposed sequential simulation strategy is proved to be more efficient than the direct simulation method for structural response bounds analysis.